(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
In Kharkiv Forest-Steppe, 24 species of Mycena are revealed with three taxa (Mycena megaspora Kauffman, M. polyadelpha (Lasch) Kühner and M. inclinata f. albopilea Derbsch et J.Aug. Schmitt ex Robich et Cons.) found in Ukraine for the first time. In general, 28 species of Mycena are given for territory studied, including data by other authors. Wood-inhabiting Mycenas dominate both qualitatively and quantitatively.